Non-Contact Measurement System Analysis for Metallurgical Slabs Proportion Parameters - Machacek, Z.; Slaby, R.; Vanus, J.; Hercik, R.; Koziorek, J. (Elektronika ir Elektrotechnika, 2013)
The article describes design and development of a measuring system that allows to measure the selected size and shape variations of a steel slabs with a defined precision. The developed measurement system allows obtaining accurate information on the dimensions of the material that enters the rolling mill. More precise information about dimensions of the material entering the rolling mill ultimately brings significant savings of the metal material. The proposed methodology of testing of different types of non-contact measurement for steel materials is used for the design and management of industrial applications with specific requirements. DOI: http://dx.doi.org/10.5755/j01.eee.19.10.5897